2021
DOI: 10.1109/access.2021.3096136
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Deep Learning Techniques for Face Recognition

Abstract: In recent years, researchers have proposed many deep learning (DL) methods for various tasks, and particularly face recognition (FR) made an enormous leap using these techniques. Deep FR systems benefit from the hierarchical architecture of the DL methods to learn discriminative face representation. Therefore, DL techniques significantly improve state-of-the-art performance on FR systems and encourage diverse and efficient real-world applications. In this paper, we present a comprehensive analysis of various F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 176 publications
0
26
0
Order By: Relevance
“…Here we used a representative DCNN for face recognition, VGG-Face (Parkhi et al, 2015 ), which is pretrained to identify faces only. In recent years, various deep learning methods have been used in face recognition systems (Fuad et al, 2021 ). Among the various methods, DCNN is the most popular deep learning method for face recognition (Fuad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we used a representative DCNN for face recognition, VGG-Face (Parkhi et al, 2015 ), which is pretrained to identify faces only. In recent years, various deep learning methods have been used in face recognition systems (Fuad et al, 2021 ). Among the various methods, DCNN is the most popular deep learning method for face recognition (Fuad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various deep learning methods have been used in face recognition systems (Fuad et al, 2021 ). Among the various methods, DCNN is the most popular deep learning method for face recognition (Fuad et al, 2021 ). Further, visual geometry group network-face (VGG-Face) is one of the most commonly used CNN models for face recognition (e.g., Ghazi and Ekenel, 2016 ; Karahan et al, 2016 ; Grm et al, 2017 ) and has shown successful performance of face recognition under various conditions (Ghazi and Ekenel, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method uses OpenCV to perform region of interest (ROI) cropping on facial images to recover an image of the non-occluded area. To avoid pixelation of the facial image after ROI processing, in which the image loses detail [13], we adopt an ESRGAN model [14] to enhance the details of the non-occluded image. ESRGAN can generate real textures and enhance detailed features through image super-resolution.…”
Section: ) Esrgan Deblurringmentioning
confidence: 99%
“…Deep Learning [13] is a series of models, technologies, and architectures based on Artificial Neural Networks which have undergone a revolution in AI in the last years. Its doubtless success in real world problems reaches areas such as face recognition [14], music composition [15] o multilingual translation [16]. In the last decade, thousands of researchers have proposed new models that overtake the achievements of previous architectures, so it is impossible to give a general framework that covers all possible approaches in deep learning.…”
Section: Deep Learning For the Detection Of Intracranial Hemorrhagementioning
confidence: 99%